THE PALYNOLOGY AND PALAEONVIRONMENT OF THE UPPER TRIASSIC DOLOMITIC-MARLY SEQUENCE OF DOGNA VALLEY (UDINE, FRIULI-VENEZIA GIULIA, NE ITALY) WITH REPTILE TRACKWAYS (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1997)
New data and considerations about the biostratigraphy and the palaeoenvironment of a section in the Late Triassic dolomitic-marly sequence which crops out in the Dogna valley (Udine, Friuli, NE Italy) are reported. In particular a unit with a surface bearing tracks of archosauromorph terrestrial reptiles has been investigated. In the layer immediately overlaying the track-bearing one, a rich palynological assemblage with Enzonalasporites vigens; Vallasporites ignacii, Patinasporites densus, Zonalasporites cinctus, Pseudoenzonalasporites summus, Samaropollenites speciosus, Camerosporites secatus and Partitisporites spp. was found, indicating a Tuvalian age (Late Carnian) . Microfloral and sedimentological evidence indicate a dry climate and a coastal depositional environment subject to repeated emersions.